2010
DOI: 10.1007/s12020-009-9306-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the alendronate on OPG/RANKL system in differentiated primary human osteoblasts

Abstract: Alendronate is a well-established treatment for osteoporosis and suppresses bone resorption by a direct effect on osteoclasts and their precursors. The effect of alendronate on osteoclasts is produced, at least in part, by the receptor activator of nuclear factor kappaB ligand (RANKL) and the osteoprotegerin (OPG) synthesized by the osteoblasts. This study analyzes the effect of alendronate in cell viability, alkaline phosphatase (ALP) activity and RANKL and OPG expression in primary human osteoblasts (hOB). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…In previous study, hMSCs treated with 40 µM FPP or 10 µM GGPP alone showed no significant effect on cell proliferation and apoptosis [34]. Five to 20 µM of FPP treatments were also used in the inhibition of zoledronic acid [5] induced mineralization in osteoblasts [31], which indicated FPP (lower than 40 µM) and GGPP (lower than 10 µM) did not affect cell proliferation individually, and GGPP (higher than 5 µM) inhibited ZA-induced mineralization. In the results of BMP-2 and Runx-2 expression, also showed no significant difference between control and 10 µM FPP or GGPP treated hBMSCs (Figure S3).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In previous study, hMSCs treated with 40 µM FPP or 10 µM GGPP alone showed no significant effect on cell proliferation and apoptosis [34]. Five to 20 µM of FPP treatments were also used in the inhibition of zoledronic acid [5] induced mineralization in osteoblasts [31], which indicated FPP (lower than 40 µM) and GGPP (lower than 10 µM) did not affect cell proliferation individually, and GGPP (higher than 5 µM) inhibited ZA-induced mineralization. In the results of BMP-2 and Runx-2 expression, also showed no significant difference between control and 10 µM FPP or GGPP treated hBMSCs (Figure S3).…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, Aln inhibited cellular proliferation at high dose in MG-63 osteoblastic cells (10 −4 M) [7] and primary human osteoblasts (<10 −5 M) [5]. The toxic doses of Aln were usually greater than 1 µM in differentiated cells, such as chondrosacrcoma cell [21], epidermal cell [22], endothelial cell [23], fibroblast [24], intestinal epithelial cell [25], or macrophage [3], [26], [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that HCV alone or in combination with other unknown factor(s) may infect and alter bone cells or their precursors in predisposed individuals. Abnormalities have been demonstrated by previous studies in the insulin-like growth factor (IGF) system (3), the receptor activator of nuclear factor kappa B ligand (RANKL) and osteoprotegerin (OPG) system imbalance (4, 5), and the transforming growth factor (TGF)–β-Smad signaling (6). With regards to therapeutic approaches to the disease, the hallmarks are the changes in deep, torturing bony pain, bone markers, thickening of the long bone cortices and BMD.…”
Section: Discussionmentioning
confidence: 99%